PENGARUH TINGKAT RELIGIUSITAS PADA KEPUTUSAN BUYING PROPERTI SYARIAH NON BANK ( STUDI KASUS PADA BUYER GRIYA BAITI JANNATI RECIDENCE ) . - Dirwan Dirwan (Jurnal Ekonomi Bisnis Syariah, 2019)
Taking one's decision to a reality and the facts that are being faced is strongly influenced by the extent to which a person understands the reality and facts he faces. The understanding is born from the process of linking between knowledge and fact or reality, from which behavior will be born, actions and attitudes that will be taken are related to the facts and reality it faces.The level of religiosity is born from the extent to which one's knowledge and understanding of the teachings of religion is believed, starting from the aspects of aqeedah, sharia, morality which ultimately are internalized in the appreciation and practice of religious teachings that are believed and implemented in the form of decisions and attitudes towards reality and facts faced in everyday life.Buyer decision to buy non-bank syariah property Griya baiti jannari residence is strongly influenced by the level of religiosity in each buyer.